2007
DOI: 10.1016/j.heares.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in the conserved C2B domain of otoferlin causes deafness in a new mouse model of DFNB9

Abstract: Mutations of the otoferlin gene have been shown to underlie deafness disorders in humans and mice. Analysis of genetically engineered mice lacking otoferlin have demonstrated an essential role for this protein in vesicle exocytosis at the inner hair cell afferent synapse. Here, we report on the molecular and phenotypic characterization of a new ENU-induced missense mutation of the mouse otoferlin gene designated Otof deaf5Jcs . The mutation is a single T to A base substitution in exon 10 of Otof that causes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 26 publications
4
62
2
1
Order By: Relevance
“…Wild-type mice were created by mating heterozygous animals; resulting wild-type mice were bred and maintained separately. Genotypes of all mice were confirmed post hoc (Longo-Guess et al 2007). Homozygous Otoferlin mutant animals will be referred to as "deaf Otoferlin mutant mice"; heterozygotes and wild-type animals will in some cases be lumped and referred to as "hearing control mice" or "Otoferlin control mice."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type mice were created by mating heterozygous animals; resulting wild-type mice were bred and maintained separately. Genotypes of all mice were confirmed post hoc (Longo-Guess et al 2007). Homozygous Otoferlin mutant animals will be referred to as "deaf Otoferlin mutant mice"; heterozygotes and wild-type animals will in some cases be lumped and referred to as "hearing control mice" or "Otoferlin control mice."…”
Section: Methodsmentioning
confidence: 99%
“…The mice studied in these experiments have a point mutation resulting in a nonconserved substitution of I319N in the second of six calcium binding domains of Otoferlin that results in the absence of its expression in cochlear hair cells (Longo-Guess et al 2007). Otoferlin is thought to sense calcium and regulate synaptic transmission by inner hair cells (Johnson and Chapman 2010;Roux et al 2006).…”
mentioning
confidence: 99%
“…A previously reported isoleucine to asparagine mutation in the C2B domain of otoferlin was found to induce severe hearing loss in mouse models (Longo-Guess et al, 2007). Although the structure of this domain is not currently known, sequence alignment with other C2 domains suggests that this mutation lies within one of the  strands of the domain.…”
Section: Point Mutations Disrupt the Function Of The C2 Domains Of Otmentioning
confidence: 95%
“…Although the structure of this domain is not currently known, sequence alignment with other C2 domains suggests that this mutation lies within one of the  strands of the domain. A previous study suggested that this mutation may disrupt folding, resulting in decreased stability and increased turnover rates within the cell (Longo-Guess et al, 2007). To investigate the functional properties of this mutant, we introduced the I318N mutation into the isolated C2B domain.…”
Section: Point Mutations Disrupt the Function Of The C2 Domains Of Otmentioning
confidence: 99%
“…This awaits differential analysis of mice with tissue-specific Ca v 1.3 deletion either in the cochlea or the brainstem. We hypothesize that the central loss has a considerable, although not exclusive impact, because other deafness-related gene mutations, which cause function loss in the cochlea, e.g., in dn/dn mice (Youssoufian et al, 2008), otoferlin otof mice (Longo-Guess et al, 2007), and prosaposin Ϫ/Ϫ mice (Akil et al, 2006), appear not to result in obvious LSO malformations. biophysical and synaptic properties analyzed, seven differed between the two phenotypes.…”
Section: Possible Causes Of the Impaired Developmentmentioning
confidence: 96%